Handbook of Military Sciences 2020
DOI: 10.1007/978-3-030-02866-4_37-1
|View full text |Cite
|
Sign up to set email alerts
|

Civil-Military Relations: What Is the State of the Field

Abstract: In the study of states and societies, civil-military relations ought to occupy a central position. It is only the armed forces that can provide for a nation's defense and at the same time are capable of overturning that nation's government. These dual powers are extraordinary and can constitute both an essential coercive asset and a potential threat to governments and citizens that must be neutralized. The goal of any state is to harness military professional power to serve vital national security interests, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The military culture can be split into “core professional values” (Huntington, 1957) and “role beliefs” (Fitch, 1998), which directly regulate military relations with civilian leaders and other sectors of society (Pion-Berlin & Dudley, 2020, p. 10). This differentiation fits well into the ACF’s (Sabatier & Weible, 2007) deep core and policy core beliefs tiers (Table 1).…”
Section: Defining Military Culture: Adapting Military Culture To Deep...mentioning
confidence: 99%
“…The military culture can be split into “core professional values” (Huntington, 1957) and “role beliefs” (Fitch, 1998), which directly regulate military relations with civilian leaders and other sectors of society (Pion-Berlin & Dudley, 2020, p. 10). This differentiation fits well into the ACF’s (Sabatier & Weible, 2007) deep core and policy core beliefs tiers (Table 1).…”
Section: Defining Military Culture: Adapting Military Culture To Deep...mentioning
confidence: 99%
“…Similarly, Jacobson (2009) found that military missions condition support for the armed forces, including popularity, assessments of progress and partisan division. In this vein, Pion-Berlin and Dudley (2020: 15) noted that ‘the US public is both enamored with the military and ignorant about it, while at the same time considerably distrustful of political leaders’. On the other hand, cynicism towards the military may be due to the lack of citizens’ military experience (especially in all-volunteer military recruitment), criticism of the military in the media, the communication gap between the military and civil society, as well as instances of military corruption and scandals (Malešič and Garb, 2018).…”
Section: Public Opinion the Armed Forces And Societymentioning
confidence: 99%